Metodização do isolamento e análise do perfil de suscetibilidade aos antimicrobianos das populações ressuscitáveis e metabolicamente ativas de Mycobacterium tuberculosis - Brunetti, Manuela Negrelli (2021)
An effective antimicrobial therapy is one of the biggest challenges in combating Tuberculosis (TB), since therapeutic failures can happen for several reasons. The bacillus that causes the disease can be found in different metabolic states in sputum samples from patients with TB, and it has been demonstrated that these bacilli in dormant states are more tolerant to some drugs and are not visualized by conventional diagnostic methods, which may justify eventual therapeutic failures for no apparent reason. This study aimed to assess whether the antimicrobial susceptibility profile of the total population (resuscitable + active) of Mycobacterium tuberculosis, isolated from sputum samples from patients with pulmonary TB, differs from the profile of the metabolically active population. The study was divided into two stages. The first consisted of standardizing the obtainment of the total population of bacilli by using a culture medium with MTB liquid culture supernatant filtrate (SN), and standardizing the Antimicrobial Susceptibility Test (AST) by the broth microdilution method. The second stage tested standardized methods for obtaining the total bacterial population using sputum samples from patients with pulmonary TB and followed by performing AST on these samples. Our results showed that the 7H9 liquid culture medium added with SN was superior to the others tested in relation to the recovery of resuscitable bacilli and with sufficient bacterial concentration to carry out the AST directly. However, due to the high contamination rate of this medium, the indirect method was used to obtain MTB populations, before the AST. The addition of SN to the 7H9 liquid growth medium has been shown to decrease the positivity time by up to 1.5 days. The use of Optical Density as a growth detection tool in liquid culture was shown to be inferior to the automated system, not having any correlation with bacterial growth. Additionally, our results showed that the washing and freezing step seems to reduce the inhibitory factors present in the sputum, by decreasing the growth inhibition rate after freezing the samples, however, it does not eliminate them. The use of SN has shown, in tests with reference strain, that it accelerates the growth of active MTB, but does not alter bacterial quantification by the Most Probable Number (MPN) technique. The AST with the total population of bacilli, although presenting higher MIC values more frequently, does not imply changes in sensitivity and resistance in the population of patients without previous treatment for pulmonary TB. Nevertheless, our results suggest that the susceptibility profile of the total population of bacilli compared to the active population, of the only case of a patient under treatment included in this study, showed possibly different sensitivity/resistance patterns in this population of patients, suggesting the need for new studies involving patients undergoing treatment with suspected resistance, therapeutic failure or relapse.